Central Asia in a reconnecting Eurasia Kazakhstan's evolving foreign economic and security interests - Kuchins, Andrew; Mankoff, Jeffrey 1977-; Kourmanova, Aitolkyn; Backes, Oliver (Center for Strategic & International Studies (CSIS) Rowman & Littlefield, 2015)
"Today, with combat operations in Afghanistan winding down, U.S. policy toward the states of Central Asia is transitioning to a third era. The United States now has an opportunity to refashion its approach to the region. In doing so, it should capitalize on trends already underway, in particular the expansion of trade and transit linkages, to help integrate Central Asia more firmly into the global economy, while also working to overcome tensions both within the region itself and among the major neighboring powers with interests in Central Asia. Central Asia in a Reconnecting Eurasia: Kyrgyzstan's Evolving Foreign Economic and Security Interests, part of a five volume series, examines the full scope of U.S. national interests in Kyrgyzstan and puts forward the broad outlines of a strategy for U.S. engagement over the coming years"--Publisher's web site